Al-Ibtikārāt fi Istikhdām Wasāil Ta’līmiyyah al-Lugah al-‘Arabiyyah Litaḥsīn al-Mahārāt al-Lugawiyyah fi 'Aṣri al-Wabā' Covid-2019 - Laila Maghfiroh; Nanik Setyowati; Tina Zulfa Suryani (Aphorisme: Journal of Arabic Language, Literature, and Education, 2021)
This research is about innovations in using Arabic language learning media to improve Arabic language skills in the sixth semester of the Islamic elementary school, Arrisalah Slahung- Ponorogo 2019-2020. In this paper, we talk about the process of teaching the Arabic language, its innovations and the benefits of its innovation in the VIB class. In the sixth semester, we need innovation, education, the Arabic language, so that students do not feel afraid to study the Arabic language. By creating this, teaching Arabic is fun and joyful and students do not feel afraid to learn Arabic. This research is qualitative , the researcher obtained data from observation, interview, and documentation in the Islamic Primary School of arrisalah. Innovation from the Latin language, innovation means renewal and change. Innovation is the idea, event, and method as something new to a community of people. Education innovation is an innovation in education or innovation to improve problems in education. So, educational innovation is the idea, method, and new state of a person or community, either discovery or interference, which is used to achieve the goals of education or to improve the problems of national education. By innovating education in the sixth semester, students' ability increases in the Arabic language lesson better than ever before. And students do not feel afraid when learning Arabic. The Arabic language lesson was fun and enjoyable for the students.